Prevalence of Refractive Errors in Urban Area among School Boys (Medical Forum Monthly, 2021)
Objective: To study the prevalence of refractive errors among school boys in urban area.Study Design: A cross sectional studyPlace and Duration of Study: This study was conducted at Ophthalmology, Bahawal Victoria Hospital, Quaid e Azam Medical College, Bahawalpur during November 2017.Materials and Methods: The study population comprised of 462 students from class 6th to Class 10th. Ocular examination process was thoroughly explained to the study participants while all the study instruments/equipments were transported to school one day prior to the actual ocular examination. Standard “Snellen Chart” was used for screening of visual acuity. Children having visual acuity < 6/6 in any of the eye were further confirmed for refractive error with the use of pinhole. Objective refraction was made using auto-refractor and retinoscopy while confirmation was done applying subjective refraction.Results: Among a total of 460 students, age range was between 9 to 18 years while the mean age +SD was recorded to be 14.3+1.8 years. History of glasses was noted among 58 (12.6%) students. There were 253 (55.0%) who had history of glasses in their parents. Findings of our study revealed frequency of refractive errors in 98 (21.3%) students. Among 98 children with refractive errors, myopia in 58 students (59.2%) was the commonest type of refractive error followed by astigmatism in 28 students (28.6%) and hypermetropia in 12 students (12.1%).Conclusion: Myopia was the commonest type of refractive error in school going boys followed by Astigmatism and hypermetropia.